Effect of pulmonary artery pressure‐guided therapy on heart failure readmission in a nationally representative cohort. (13th May 2022) - Kishino, Yoshikazu; Kuno, Toshiki; Malik, Aaqib H.; Lanier, Gregg M.; Sims, Daniel B.; Ruiz Duque, Ernesto; Briasoulis, Alexandros
Abstract: Aims: Pulmonary artery pressure (PAP)‐guided therapy in patients with heart failure (HF) using the CardioMEMS (CMM) device, an implantable PAP sensor, has been shown to reduce HF hospitalizations in previous studies. We sought to evaluate the clinical benefit of the CMM device in regard to 30, 90, and 180 day readmission rates in real‐world usage. Methods and results: We queried the Nationwide Readmissions Database (NRD) to identify patients who underwent CMM implantation (International Classification of Diseases 9 and 10 codes) between the years 2014 and 2019 and studied their HF readmissions. Moreover, we compared CMM patients and their readmissions with a matched cohort of patients with HF but without CMM. Multivariable Cox regression analysis was performed to adjust for other predictors of readmissions. Prior to matching, we identified 5 326 530 weighted HF patients without CMM and 1842 patients with CMM. After propensity score matching for several patients and hospital‐related characteristics, the cohort consisted of 1839 patients with CMM and 1924 with HF without CMM. Before matching, CMM patients were younger (67.0 ± 13.5 years vs. 72.3 ± 14.1 years, P  < 0.001), more frequently male (62.7% vs. 51.5%, P  < 0.001), with higher rates of prior percutaneous coronary intervention (16.9% vs. 13.2%, P  = 0.002), peripheral vascular disease (29.6% vs. 17.8%, P  < 0.001), pulmonary circulatory disorder (38.7% vs. 23.2%, P  < 0.001), atrial fibrillation (51.2% vs. 45.3%, P  = 0.002), prior left ventricular assist device (1.8% vs. 0.2%, P  < 0.001), high income (32.2% vs. 16.4%, P  < 0.001), and acute kidney disease (43.8% vs. 29.9%, P  < 0.001). Readmission rates at 30 days were 17.3% vs. 20.9% for patients with vs. without CMM, respectively, and remained statistically significant after matching (17.3% vs. 21.5%, P  = 0.002). The rates of 90 day (29.6% vs. 36.5%, P  = 0.002) and 180 day (39.6% vs. 46.6%, P  = 0.009) readmissions were lower in the CMM group. In a multivariable regression model, CMM was associated with lower risk of readmissions (hazard ratio 0.75, 95% confidence interval 0.63–0.89, P  = 0.001). Conclusions: The CMM device was associated with reduced HF rehospitalization rates in a nationally representative cohort of HF patients, validating the clinical trial that led to the approval of this device and its utilization in the treatment of HF.